Labor markets and cultural values: Evidence from Japanese and American views about caregiving immigrants1. (18th July 2019) - Peters, Margaret E.; Kage, Rieko; Rosenbluth, Frances; Tanaka, Seiki
Abstract: One overlooked reason for the persistence of distinct cultural values across rich democracies, we argue, is a country's labor market structure. Parents seeking to position their children for long‐term success would do well to instill values consistent with requirements of the labor market in the country where their children are likely to work. To the extent that labor markets are fluid, as in the United States, parents should teach their children to be resourceful and creative. In countries like Japan with relatively rigid labor markets, where workers have one chance to land a long‐term contract with a leading company, parents instead should instill the values of hard work and respect for authority. We find evidence consistent with this argument in survey experiments about attitudes in the United States and Japan about the desirability of employing immigrants for care work, and what values the immigrant care workers should hold. We also find evidence of indirect norm creation. American and Japanese respondents prefer immigrants—not just caregiving immigrants—whose values align with their country's type of valued human capital.